Digital Transformation and Technological Innovation in the National Banking Sector: A Grounded Theory Approach - Abdul Wahab; Izaac L. D Lawalata; Faisal Fattah; Megawaty Megawaty (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study explores the dynamics of digital transformation and technological innovation in Indonesia’s banking sector by examining how innovation is created, adopted, and interpreted within banking organizations. Research Method: A qualitative Grounded Theory approach was employed. Data were collected through in-depth interviews, non-participant observations, and document analysis at selected state-owned and Islamic banks in Makassar, Indonesia. Data were analyzed using open, axial, and selective coding, supported by constant comparison and theoretical memoing. Results and Discussion: The findings show that sustainable digital transformation is shaped by the interaction of four main elements: leadership vision, organizational culture, technological integration, and human adaptability. These elements reinforce one another in directing strategy, fostering an innovation-oriented environment, and enabling employees to adjust to digital change. From these patterns, the study formulates the substantive theory of Adaptive Organizational Synergy. Implications: This study enriches innovation and digital transformation literature by emphasizing organizational and interpretive dynamics. In practice, it provides guidance to policymakers and banking leaders on designing human-centered digital transformation strategies. Future studies are recommended to test this theory across regions, banking models, and wider digital ecosystems.